Mast Cells Positive to Tryptase and c-Kit Receptor Expressing Cells Correlates with Angiogenesis in Gastric Cancer Patients Surgically Treated. (20th November 2013) - Ammendola, Michele; Sacco, Rosario; Sammarco, Giuseppe; Donato, Giuseppe; Zuccalà, Valeria; Romano, Roberto; Luposella, Maria; Patruno, Rosa; Vallicelli, Carlo; Verdecchia, Giorgio Maria; Cavaliere, Davide; Montemurro, Severino; et al.
Abstract : Background . Angiogenesis is a complex process involved in both growth and progression of several human and animal tumours. Tryptase is a serin protease stored in mast cells granules, which plays a role in tumour angiogenesis. Mast cells (MCs) can release tryptase following c-Kit receptor (c-KitR) activation. Method . In a series of 25 gastric cancer patients with stage T3 N 2 - 3 M0 (by AJCC for Gastric Cancer 7th Edition), immunohistochemistry and image analysis methods were employed to evaluate in the tumour tissue the correlation between the number of mast cells positive to tryptase (MCPT), c-KitR expressing cells (c-KitR-EC), and microvascular density (MVD). Results . Data demonstrated a positive correlation between MCPT, c-KitR-EC, and MVD to each other. In tumour tissue the mean number of MCPT was 15, the mean number of c-KitR-EC was 20, and the mean number of MVD was 20. The Pearson test correlating MCPT and MVD, c-KitR-EC and MVD was significantly (r = 0.64, P = 0.001 ; r = 0.66, P = 0.041, resp.). Conclusion . In this pilot study, we suggest that MCPT and c-KitR-EC play a role in gastric cancer angiogenesis, so we think that several c-KitR or tryptase inhibitors such as gabexate mesilate and nafamostat mesilate might be evaluated in clinical trials as a new antiangiogenetic approach.